Synthesis in living cells with the assistance of supramolecular nanocarriers. Issue 39 (1st April 2016) - Ragab, Sherif Shaban; Thapaliya, Ek Raj; Zhang, Yang; Tang, Sicheng; McMahan, Jeffrey Blye; Syed, Sheyum; Captain, Burjor; Raymo, Françisco M.
Abstract : Supramolecular nanocarriers transport complementary reactants inside living cells in consecutive internalization steps to allow their reaction exclusively in the intracellular space with the formation of a fluorescent product. Abstract : Independent supramolecular nanocarriers can transport pairs of complementary reactants inside living cells in two consecutive incubation steps. After the second internalization step, the nonemissive reactants produce a fluorescent product with the concomitant appearance of intense fluorescence exclusively in the intracellular space. These results demonstrate that supramolecular delivery can be exploited to perform chemical reactions inside target cells and can lead to valuable strategies for the intracellular synthesis of drugs.